2011
DOI: 10.1057/crr.2011.10
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Disclosure and Reputation: A Comparative Study

Abstract: Drawing on legitimacy theory, we discuss that a company's reputation is a determinant of sustainability disclosure. Specifically, we consider the concept of reputation into three dimensions for analysis: stakeholders' commitment, financial performance and media exposure. This paper differs from previous social and environmental reporting studies in that it investigates both internal and external contextual factors that influence disclosure practice. We claim that companies with a good financial performance, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
203
2
62

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(289 citation statements)
references
References 49 publications
4
203
2
62
Order By: Relevance
“…This group reported either to the Governance Committee of the company"s board of directors or to a high-ranking officer within the company. This was a good sign since past research indicated that companies where social responsibility was on the board of directors" agenda were likely to make more sustainability disclosures (Michelon, 2011). Many committees consisted of senior level managers from different areas of the company, thus demonstrating a company-wide presence of sustainability thinking.…”
Section: Sample Selection and Collection Of Datamentioning
confidence: 92%
See 1 more Smart Citation
“…This group reported either to the Governance Committee of the company"s board of directors or to a high-ranking officer within the company. This was a good sign since past research indicated that companies where social responsibility was on the board of directors" agenda were likely to make more sustainability disclosures (Michelon, 2011). Many committees consisted of senior level managers from different areas of the company, thus demonstrating a company-wide presence of sustainability thinking.…”
Section: Sample Selection and Collection Of Datamentioning
confidence: 92%
“…They are frequently subject to public attention simply because of (a) the volume of their businesses; (b) their reach across the globe in terms of the widely scattered sources of materials and labor that they access; (c) the geographically dispersed markets where they sell their products and services; (d) their potential to make a large impact on their physical and social environment; and (e) the extensively diverse communities that they serve. Over the past few decades, researchers have found that companies that were large in size and were otherwise in the public"s eyes tended to make more voluntary disclosures of sustainability (Belkaoui & Karpik1989;Cowen, Ferreri, & Parker 1987;Patten 1991;Roberts 1992;Hackston & Milne 1996;Cormier & Gordon 2001;Huafang & Jianguo 2007;Michelon 2011;Gamerschlag et al 2011;and Chan, Watson & Woodliff 2014). Globally, Chu, Chatterjee and Brown"s (2013) study showed that larger Chinese companies disclosed more information about their greenhouse gas emissions than their smaller counterparts, and more recently, Herbohn, Walker and Loo (2014) studied the link between sustainability disclosure and sustainability performance in the Australian extractive industries to find that firm size was positively associated with sustainability.…”
Section: Sample Selection and Collection Of Datamentioning
confidence: 99%
“…Recently, Michelon (2011) has focused attention on the necessity to improve the comprehension about the relationship between Corporate Sustainability Disclosure (CSD) and CR. In particular, Michelon analysed the concept of reputation along three dimensions: Commitment to stakeholders, financial performance and media exposure.…”
Section: Sustainability Reporting and Corporate Reputation: An Additimentioning
confidence: 99%
“…This practice, on one hand helps to alleviate institutional pressure to increase the effectiveness of market discipline and on the other facilitating the "control" of key stakeholders through an effective management of CR (Barnett et al, 2006). Recent studies based on legitimacy theory have also shown that it is more likely to use social reporting tools for those companies that adopt a proactive strategy for the stakeholder expectations and that have good financial performance and are exposed to a significant media pressure; this allows them to increase the degree of social legitimacy and their reputation at the widest audience of stakeholders (Michelon, 2011). Additional contributions addressing risk management and voluntary disclosure have different results (Xifra and Ordeix, 2009).…”
Section: Sustainability Reporting and Corporate Reputation: An Additimentioning
confidence: 99%
“…In terms of the theoretical approach, the paper refers to Abeysekera (2006) who outlines the development of a theoretical framework underlying IC disclosure. Theories that have been considered include legitimacy and stakeholder (Guthrie, Petty, Yongvanich, & Ricceri, 2004;Abeysekera & Guthrie, 2005;Michelon, 2011), signalling (Bozzolan, Favotto, & Ricceri, 2003;Garcia-Meca & Martinez, 2005;Shi, Kim, & Magnan, 2014), resource based (Barney, 2001;Palmer, 2008), agency (Bozzolan et al, 2003;Garcia & Martinez, 2005) and information asymmetry (Amir & Lev, 1996;Lang & Lundholm, 2000). Although the IC literature illustrates the application of various theoretical approaches, the general disclosure literature has overall indicated a close association with agency and signalling theories.…”
Section: Voluntary Disclosure Framework and The Conceptual Frameworkmentioning
confidence: 99%